Limited antitumor activity of combined BET and MEK inhibition in neuroblastoma. Issue 6 (19th April 2020) - Healy, Jason R.; Hart, Lori S.; Shazad, Alexander L.; Gagliardi, Maria E.; Tsang, Matthew; Elias, Jimmy; Ruden, Jacob; Farrel, Alvin; Rokita, Jo Lynne; Li, Yimei; Wyce, Anastasia; Barbash, Olena; et al.
Abstract: Background: The treatment of high‐risk neuroblastoma continues to present a formidable challenge to pediatric oncology. Previous studies have shown that Bromodomain and extraterminal (BET) inhibitors can inhibit MYCN expression and suppress MYCN ‐amplified neuroblastoma in vivo. Furthermore, alterations within RAS‐MAPK (mitogen‐activated protein kinase) signaling play significant roles in neuroblastoma initiation, maintenance, and relapse, and mitogen‐activated extracellular signal‐regulated kinase (MEK) inhibitors demonstrate efficacy in subsets of neuroblastoma preclinical models. Finally, hyperactivation of RAS‐MAPK signaling has been shown to promote resistance to BET inhibitors. Therefore, we examined the antitumor efficacy of combined BET/MEK inhibition utilizing I‐BET726 or I‐BET762 and trametinib in high‐risk neuroblastoma. Procedure: Utilizing a panel of genomically annotated neuroblastoma cell line models, we investigated the in vitro effects of combined BET/MEK inhibition on cell proliferation and apoptosis. Furthermore, we evaluated the effects of combined inhibition in neuroblastoma xenograft models. Results: Combined BET and MEK inhibition demonstrated synergistic effects on the growth and survival of a large panel of neuroblastoma cell lines through augmentation of apoptosis. A combination therapy slowed tumor growth in a non‐ MYCN –amplified, NRAS ‐mutated neuroblastoma xenograft model, but had no efficacy in an MYCN ‐amplified model harboring a loss‐of‐function mutation in NF1 . Conclusions: Combinatorial BET and MEK inhibition was synergistic in the vast majority of neuroblastoma cell lines in the in vitro setting but showed limited antitumor activity in vivo. Collectively, these data do not support clinical development of this combination in high‐risk neuroblastoma.